Defensoria pública e regularização fundiária urbana de interesse social: novos rumos à efetivação do direito fundamental social à moradia - Nascimento, Bruno Pereira (2014)
The historical absence of public land policies aimed at production of social housing, together with the strong speculation promoted by an elitist market, segregated the paucity of financial resources in large illegal and informal areas of Brazilian cities population. Moreover, this process of urbanization led to the exclusion of residents of such areas, with a new mapping of cities, dividing into civilian areas (formal/legal) and uncivil areas (informal/illegal/wild). Since the inclusion of the right to housing in the list of fundamental social rights in the Constitution by Constitutional Amendment nº 26/2000, diplomas were issued several regulations in order to ensure the full development of such a basic need. However, the legal achievements of several decades did not represent a substantial change in the Brazilian urban reality, just pay attention to the unsanitary conditions in the cities, open sewage, bad housing conditions for huge part of the population living in settlements huddled in cubicles informal. In this scenario, assume proposals that promote the empowerment of vulnerable social groups inhabiting these communities in order to give them the full enjoyment of fundamental social right to housing special mention. Also, the Public Defender has a major role in the effectiveness of urban land regularization of informal settlements social interest, given the capacity for dialogue and rapprochement with social movements and members of such communities .